Advanced case of PKDL due to delayed treatment: A rare case report - Topno, Roshan Kamal (PLoS Negl Trop Dis, 2020)
Post-kala-azar dermal leishmaniasis (PKDL) is clinical outcome of visceral leishmaniasis (VL) and is thought to be the potential reservoir of parasite. Miltefosine (MF) is the only oral drug existing for treatment of post-kala-azar dermal leishmaniasis (PKDL). Increased miltefosine tolerance in clinical isolates of Leishmania donovani has been reported and is one of the major concerns in the treatment of PKDL. Here, we report a highly ulcerated PKDL case that was successfully cured after miltefosine treatment.